IL-2/JES6-1 mAb complexes dramatically increase sensitivity to LPS through IFN-γ production by CD25+Foxp3- T cells - Tomala, Jakub; Weberova, Petra; Tomalova, Barbora; Jiraskova Zakostelska, Zuzana; Sivak, Ladislav; Kovarova, Jirina; Kovar, Marek (eLife, 2021)
Complexes of IL-2 and JES6-1 mAb (IL-2/JES6) provide strong sustained IL-2 signal selective for CD25+ cells and thus they potently expand Treg cells. IL-2/JES6 are effective in the treatment of autoimmune diseases and in protecting against rejection of pancreatic islet allografts. However, we found that IL-2/JES6 also dramatically increase sensitivity to LPS-mediated shock in C57BL/6 mice. We demonstrate here that this phenomenon is dependent on endogenous IFN-γ and T cells, as it is not manifested in IFN-γ deficient and nude mice, respectively. Administration of IL-2/JES6 leads to the emergence of CD25+Foxp3-CD4+ and CD25+Foxp3-CD8+ T cells producing IFN-γ in various organs, particularly in the liver. IL-2/JES6 also increase counts of CD11b+CD14+ cells in the blood and the spleen with higher sensitivity to LPS in terms of TNF-α production and induce expression of CD25 in these cells. These findings indicate safety issue for potential use of IL-2/JES6 or similar IL-2-like immunotherapeutics.
Keywords: interferon gama; LPS; Interleukin-2; Interferon-gamma; Mice, Inbred BALB C; mouse; T cells; Lipopolysaccharides; inflammation; myši inbrední C57BL; mužské pohlaví; Mice; interleukin-2; hyperreactivity; IFN-γ; immunology; Mice, Nude; ženské pohlaví; zvířata; il-2/anti-il-2 mab complexes; lipopolysacharidy; CD25; myši nahé; myši inbrední BALB C; myši; Female; Mice, Inbred C57BL; Male; Animals